Effects of ascorbic acid on intestinal flora and metabolites of C57 mice exposed to formaldehyde in digestive tract - Xin Ling; Ziyan Hao; Yixuan Shi; Yuting Li; Kehan Wang; Yunshan Zhang; Yue Wang (PLoS ONE, 2025)
The diversity of microbiota and metabolites plays a key role in regulating metabolism, host immune response, neurobehavioral effects and detoxification mechanism in the digestive tract gut. Formaldehyde (FA) affects the gastrointestinal tract and its microbiota, whereas ascorbic acid (VC) improves gut health and selectively promotes microbial growth. In this study, we employed 16S rRNA sequencing and non-targeted metabolomics approaches to investigate these interactions. Our results demonstrated that Lachnospiraceae_NK4A136_group, Lactobacillus, Ligilactobacillus, Clostridiales_unclassified, and other microflora significantly decreased following FA exposure, whereas the intestinal flora changed in the exact opposite way following VC administration. And compared with FA group, the number of 492 ions were regulated, in which 382 feature was up-regulated and 304 feature was down-regulated in FA + 150 mg VC group. In addition, a correlation between gut microbiota and metabolites was observed. These results reveal the effects of FA or VC on the gastrointestinal tract and its microbiota, and our understanding in the treatment of FA-induced damage to the digestive tract.